Development of A Learning Module Based on Local Wisdom of Bangkalan - Karimah; Setyawan, Agung; Handika, Ilham (Citra Dharma Cindekia, 2025)
The research aims to develop learning module in the hope that they can help students' understanding of the material in class III, chapter V, IPAS lessons, the topic of natural and artificial appearances in my area through a science and social science learning module based on Bangkalan local wisdom. The subjects of this research were 17 class III students at SDN Dabung 1 Geger for the 2024/2025 academic year. This research uses the Research and Development (R&D) method with a 4D development model, namely, 1) define, 2) design, 3) development and 4) dessiminate. The data collection techniques used were interviews, observation and questionnaires. The results obtained include validation of learning design experts of 90% with the very valid category, validation of teaching materials experts of 90% with the very valid category, validation of material experts of 97% with the very valid category and validation of language experts of 77.5% with the valid category. The results of the calculation of observations of learning implementation show a percentage of 100% which is categorized as implemented, the student's learning completeness score with the highest score of 100 and the lowest 70 gets the complete category, so it can be concluded that the learning module is said to be effective by reviewing observations of learning implementation and learning results tests. The results of the response questionnaire based on practicality got a score of 89% responses from students and got 92% responses from teachers, both data are in a very practical category.